INFLUENCE OF FUNCTIONAL ABILITY IN RUNNING 400 AND 800 METERS - Abdulla Elezi; Hasim Rushiti; Afrim Koca (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2013)
Goal of the research was to assess on the grounds of data collected that were used to assess the functional ability of the cardio-respiratory system and the results of running to determine the relation of these sum of variables. Basic statistical indicators of the physiological variables and results of running were calculated. For determining the relation, the regression analysis was used in the manifested space. Criterion variable (running for 100 meters) did not demonstrate statistically significant coefficient of multiple variation with predictor variables. The time span in running 400 meters is short in order to engage mechanisms that supply and transform the energy for oxidative processes. Criterion variable (of running 800 meters) has demonstrated statistically significant coefficient of multiple correlations with predictor variable and its value was 0.377 tested through F-test. This is understandable given that the time effect of engagement of systems responsible for transfer and transformation of energy compared to time needed for running 400 meters.